DIDACTIC ASPECTS OF MS POWER POINT USAGE - Raspopov В.Б.; Manzhula А.М. (Journal of Information Technologies in Education (ITE), 2011)
This paper discusses the usage of triggers in interactive presentations for educational purposes, in particular, in didactic games and other software, which are useful for test control and education. These tools may be used by teachers and students, who develop educational software using MS Power Point.